Kepastian Hukum Hak Imunitas dalam Pertanggungjawaban Rumah Sakit Berdasarkan Undang-Undang No17 Tahun 2023 Tentang Kesehatan - Damanik, Torangin; Syofyan, Syofirman; Yussy Adelina Mannas (Universitas Ekasakti, 2024)
In the healthcare service process, hospitals often face legal issues. This involves actions by hospitals that tend not to meet the expectations of patients or their families. The issues addressed in this research are: first, how is the legal certainty of hospital immunity rights regulated in health laws? Second, how is legal protection provided to patients who suffer losses due to negligence or errors by hospitals related to immunity rights under health laws? The research method used is a Juridical Normative/doctrinal approach that examines legislative approaches with literature study data collection techniques. The findings of this research conclude that: firstly, hospitals have been granted adequate legal immunity protection as stated in Article 192 paragraphs 1 and 2, where hospitals are immune as long as they do not violate laws and ethical codes, using immunity to carry out their duties. Secondly, hospitals are responsible for negligence by healthcare personnel causing patient harm, thus hospitals operate according to operational and healthcare service standards to minimize negligence resulting in patient harm. The hospital's responsibility towards patients suffering losses is governed by Article 193 of the Health Law.